2005
DOI: 10.1007/s10620-005-2713-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects of Partially Hydrolyzed Guar Gum on Symptoms and Quality of Life of Patients with Irritable Bowel Syndrome. A Multicenter Randomized Open Trial

Abstract: The effects of partially hydrolyzed guar gum (PHGG) were compared in patients with irritable bowel syndrome, at 10 g/day (N = 40) and 5 g/day (N = 46) for 12 weeks. Gastrointestinal symptoms (GSRS), quality of life (SF-36), and psychological symptoms (HADS) were evaluated at baseline, during treatment (months 1 and 3), and at follow-up (month 6). In both groups symptoms and quality of life improved significantly after the first month of administration until follow-up compared to those at baseline. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…56 The main component of PHGG is galactomannan, which softens stool, improves fecal output, and increases bulk capacities. 57 PHGG treatment in IBS children found a reduced frequency in IBS symptoms, but pain intensity was not decreased. 24 Results of an open-label PHGG trial in adult patients with IBS produced significant improvements in gastrointestinal symptoms, quality of life, and psychological distress, but the effects tended to diminish after the 12-week treatment period.…”
Section: Alternative Medicinementioning
confidence: 84%
See 1 more Smart Citation
“…56 The main component of PHGG is galactomannan, which softens stool, improves fecal output, and increases bulk capacities. 57 PHGG treatment in IBS children found a reduced frequency in IBS symptoms, but pain intensity was not decreased. 24 Results of an open-label PHGG trial in adult patients with IBS produced significant improvements in gastrointestinal symptoms, quality of life, and psychological distress, but the effects tended to diminish after the 12-week treatment period.…”
Section: Alternative Medicinementioning
confidence: 84%
“…24 Results of an open-label PHGG trial in adult patients with IBS produced significant improvements in gastrointestinal symptoms, quality of life, and psychological distress, but the effects tended to diminish after the 12-week treatment period. 57 Malabsorption and intolerance to carbohydrates such as fructose and lactose are believed to cause symptoms such as bloating, diarrhea, and abdominal pain. 55 However, neither lactose nor fructose intolerance was established as a cause of pain in 220 children with RAP in a recent study, 58 and lactose restriction did not improve symptoms in pediatric trials.…”
Section: Alternative Medicinementioning
confidence: 99%
“…Using lactulose breath tests (LBT), Pimental and colleagues showed that 78% of IBS patients had SIBO [128] and that eradication with a seven-day course of neomycin was associated with a significant reduction in symptoms [129] . However, these results are somewhat controversial, as both the accuracy of the LBT and its ability to gauge treatment response has been questioned [130][131][132][133] . More recently, Posserud and colleagues conducted a study of 162 IBS patients using cultures of jejunal aspirates to detect SIBO [134] .…”
Section: Antibioticsmentioning
confidence: 99%
“…9,21 Guar gum is a mucilage derived from the seeds of the Indian cluster bean Cyamopsis tetragonolobus and used in food processing as a thickener and emulsion stabilizer. 9,22 Soluble fiber is derived primarily from fruits and grains; oats are 50% soluble. 18 Soluble fiber produces viscous solutions that delay gastric emptying and small intestinal absorption and are fermented, in the proximal colon, by bacteria to a greater extent than insoluble fiber.…”
Section: Fibermentioning
confidence: 99%
“…There have been a number of trials of either fiber supplementation or bulking agents for IBS 22,28,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Table 2). Most of these trials were done between 1976 and 1994.…”
Section: Fiber Trialsmentioning
confidence: 99%